A systematic review of the cost-effectiveness of community and population interventions to reduce the modifiable risk factors for dementia. (December 2022) - Walsh, Sebastian; Brain, Jacob; Mukadam, Naaheed; Anderson, Robert; Greene, Leanne; Govia, Ishtar; Kuhn, Isla; Anstey, Kaarin J.; Knapp, Martin; Stephan, Blossom C.M.; Brayne, Carol
Highlights: Population-based health and lifestyle interventions, which change societal conditions such that everyone across a given community is more likely to live more healthily, have been under-researched within the context of dementia prevention and risk reduction. This systematic review finds such interventions highly cost-effective, and often also cost-saving, in both high- as well as low- and middle-income settings. The strongest evidence base was for interventions that changed the physical environment to decrease physical inactivity or obesity, financial interventions that improved access to or resources for education, and mass media programmes that changed the social environment around smoking. Abstract: Dementia is a leading global cause of morbidity and mortality. Evidence suggests that tackling modifiable lifecourse risk factors could prevent or delay a significant proportion of cases. Population- and community-based approaches change societal conditions such that everyone across a given community is more likely to live more healthily. We systematically reviewed economic studies of population- and community-based interventions to reduce modifiable lifecourse risk factors for dementia. We searched Medline, EMBASE, Web of Science, CINAHL, PsycInfo, Scopus, Econlit, ERIC, the British Education Index, and Google, on 03/03/2022. We included cost-effectiveness, cost-benefit, and cost-utility studies, provided that the direct outcome of the intervention was a modifiable risk factor for dementia, and was measured empirically. Quality appraisal was completed using the Consensus on Health Economic Criteria checklist. A narrative synthesis was performed. We included 45 studies, from 22, 749 records identified. Included studies targeted smoking (n = 15), education (n = 10), physical inactivity (n = 9), obesity (n = 5), air pollution (n = 2), traumatic brain injury (n = 1), and multiple risk factors (n = 3). Intervention designs included changing the physical/food environment (n = 13), mass media programmes (n = 11), reducing financial barriers or increasing resources (n = 10), whole-community approaches (n = 6), and legislative change (n = 3). Overall, interventions were highly cost-effective and/or cost-saving, particularly those targeting smoking, educational attainment, and physical inactivity. Effects were observed in high- (e.g. USA and UK) and low- and middle-income (e.g. Mexico, Tanzania, Thailand) countries. Further research into the direct effects of targeting these risk factors on future dementia prevalence will have important economic, social and policy implications.